Prevalence of Enterobius vermicularis among Primary School Children of Barangay Gravahan, Matina, Davao City - Isleta, Xhyla Zyfanne L.; Nazareno, Jambie D.; Baloca, Khian Doreen P.; Solano, Roel Nickelson M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Enterobiasis, commonly known as pinworm infection, is caused by the roundworm Enterobius vermicularis, and is considered the most prevalent parasitic infection in humans worldwide. This study aims to determine the prevalence of Enterobius vermicularis among primary school children in Barangay Gravahan, Matina, Davao City. The researchers utilized a Quantitative Correlational Research Design to determine if there is a significant association between the participants’ demographic profile and the prevalence of Enterobiasis, using a Chi-Square Test for Association. A purposive sampling technique was used to select children aged 6-12 from different households in Barangay Gravahan, Matina as study participants. Specimen collection was conducted early in the morning using the adhesive cellophane tape method. Results showed an overall prevalence of 35.0% for Enterobiasis, with 14 out of 40 samples testing positive for Enterobius vermicularis eggs. Additionally, the study found no significant correlation (p-value: >0.05) between the prevalence of Enterobiasis and the participants' demographic profile. The results highlighted that Enterobius vermicularis remains a significant health issue for children aged 6-12. To help prevent its spread, it is important to practice good hand hygiene, avoid habits that can spread pinworm eggs (such as nail biting), and taking daily morning showers to remove any eggs deposited overnight.